Planejamento institucional e projeto pedagógico nas universidades federais brasileiras - Peter, Maria da Glória Arrais (2007)
The Brazilian federal universities need to reflect in order to create a new academic, administrative and politic project, as well as about its proper practices, searching to construct a new project of university that privileges both pedagogical and social political aspect, under the paradigm of the communication. Based on the importance of the public higher education and the quality in the educational and social context of the country, the present work intends to identify, analyze and consolidate elements considered essential in order to formulate goals of planning in the Brazilian federal universities, based on adequate model of rationality seeing to the nature of the educational and scientific activity, in order to conceive a pedagogical project to public universities, in the current social, cultural, politic and economic Brazilian context. The option for a more including concept of reason, in an emancipative perspective, appeared with the intention to develop an epistemological research over the Habermas` work concerning the communicative rationality or Theory of the Communicative Action. An approach of the Habermas´ philosophical project brings the understanding of the necessity of a deeper and critical reflection, concerning about all the elements that compose the university planning, questioning its relevancy and validity, thus making possible a change in the status quo. Thus, the experiences of the diverse Brazilian federal universities had been analyzed about the elaboration and implementation of institutional plans, searching to identify the contemplated pedagogical aspects. The study evidenced that the details of the documents that consolidates the institutional planning in the Brazilian federal universities, still fail about its thesis formulated adherence that a process of this nature will have to discharge in the construction of an institutional pedagogical project, guided for a conception of university and society that critically reflects on knowing that it transmits and also on its subjective practices form, basically about the institutional project, dimension not contemplated in a forceful form in the analyzed institutions as a reflection about institutional practices. The data had allowed affirming that there is a great gap in this aspect, evidenced for the lack of proposals that deal with the teaching work, factor of extreme relevance of the intentional process of formation developed in the federal universities.